2009
DOI: 10.1002/mus.21206
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic variability of chronic inflammatory demyelinating polyneuropathy with different diagnostic criteria: Study of a UK population

Abstract: Epidemiologic data on chronic inflammatory demyelinating polyneuropathy (CIDP) is limited, and previous studies have shown variable results. The frequencies of CIDP subtypes remain unknown. Variations due to use of different diagnostic criteria have not been studied. We examined the prevalence and incidence of CIDP in Leicestershire and Rutland, UK (population 963,600). Prevalence day was 1 May 2008. The prevalence of CIDP fulfilling the 2006 clinical and electrophysiologic European Federation of Neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
106
5
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 22 publications
14
106
5
6
Order By: Relevance
“…The results are similar to the current study, even if not directly comparable, since they also included 'possible' CIDP [4] .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results are similar to the current study, even if not directly comparable, since they also included 'possible' CIDP [4] .…”
Section: Discussionsupporting
confidence: 79%
“…Recent population-based studies report an incidence of 0.4-1.6 per 100,000 population, but inclusion criteria vary [2][3][4] . Few studies have reported long-term outcome of CIDP patients [2,5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Распространенность ХВДП в юго-восточной части Объединенного Королевства Великобритании и Северной Ирландии колебалась от 1 до 7,1 на 100 тыс. [41,42,44,45].…”
Section: Introductionunclassified
“…1 Its reported incidence is variable, with recent analyses suggesting figures between 0.50 and 1.60 per 100,000 per year. 1,2 In its typical form, the disorder is symmetric and involves both proximal and distal limb regions. There are rarer atypical forms, also known as Lewis-Sumner syndrome, which can produce predominantly uni-or multifocal as well as distal involvement.…”
Section: Introductionmentioning
confidence: 99%